Low-cost grain flaking - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
The advantages of flaking grain are well known - the process reduces thickness and increases surface area so improving water absorption and cooking quality. But although the process is simple, most machines are expensive. A simple, low-cost machine...